Hard magnetic material with strong perpendicular anisotropy and preparation and application thereof
By adopting the RxA1-xBO2.5 material structure and using the alternate stacked Co-O tetrahedral and Co-O octahedral structure, the problem of difficult to obtain a material in the prior art that has both strong perpendicular magnetic anisotropy and hard magnetic characteristics is solved, and the strong perpendicular magnetic anisotropy and hard magnetic characteristics of the material are achieved, and the saturation magnetization and coercive field are effectively regulated.
Patent Information
- Application Number
- CN202311169716.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
It is difficult to obtain materials with strong perpendicular magnetic anisotropy and hard magnetic properties in the prior art, and the commonly used methods are complex and have limited effects.
The material structure of RxA1-xBO2.5 is adopted, where R is a lanthanide element, A is a main group IIA, and B is a 3d transition metal element. Through alternate stacking of Co-O tetrahedral and Co-O octahedral structures, a hard magnetic material with strong perpendicular magnetic anisotropy is formed.
The strong perpendicular magnetic anisotropy and hard magnetic properties of the material are achieved, and the saturation magnetization and coercive field are regulated through temperature regulation and doping of rare earth elements.
Smart Images

Figure CN119601328A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to but is not limited to a hard magnetic material with strong perpendicular anisotropy, and in particular to but is not limited to a hard magnetic material with strong perpendicular anisotropy and its preparation and application. Background Art
[0002] Ferromagnetic materials will show "easy" and "difficult" directions when magnetized, that is, the energy required for the magnetization process of ferromagnetic materials will vary with the relative direction of the external magnetic field and the crystal axis, so that the magnetic material exhibits magnetic anisotropy. From the perspective of technology and application, magnetic anisotropy is one of the most important characteristics of magnetic materials. Depending on the type of application, materials with different degrees of magnetic anisotropy have their own application fields, such as information magnetic storage media and permanent magnetic materials. And thin film magnetic materials with perpendicular magnetic anisotropy are easy to magnetize along the normal direction of the film surface. This thin film magnetic material with perpendicular magnetic anisotropy has attracted much attention due to its wide application prospects in the field of magnetic recording media. Films with magnetocrystalline anisotropy are an ideal carrier for realizing perpendicular recording media.
[0003] The existing methods for obtaining perpendicular magnetic anisotropy materials usually include constructing multilayer films of magnetic transition metals and oxides, such as the classic out-of-plane magnetized Ta / CoFeB / MgO system. For oxide systems, regulating the torsion of oxygen octahedrons can also have a significant regulatory effect on magnetic anisotropy, such as constructing (La 1-x Sr x MnO3) / (SrIrO3) superlattice, regulating La 1- x Sr x The MnO3 octahedron is twisted, thereby realizing perpendicular magnetic anisotropy in the system; applying compressive stress to the film is also an important means to obtain perpendicular magnetic anisotropic films, such as La 0.7 Sr 0.3 The MnO3 thin film is grown on a LaAlO3 single crystal substrate; for the thin film system, the magnetic easy axis of the thin film material synthesized by the prior art is usually located in the in-plane direction due to the shape anisotropy effect, and usually does not have strong perpendicular magnetic anisotropy.
[0004] The means of constructing multilayer films of magnetic transition metals and oxides require the construction of multilayer film structures, which are complex technical processes; the means of regulating the torsion of oxygen octahedrons in oxides are limited, and interface regulation means including superlattices require extremely sophisticated thin film growth technology; applying compressive stress to the film requires the selection of a suitable single crystal substrate for the film, and the types of single crystal substrates that can provide suitable stress for the film are usually limited. Moreover, the perpendicular magnetic anisotropy material system obtained by the above means usually does not have hard magnetic properties. Obtaining materials with intrinsic perpendicular magnetic anisotropy has always been the direction of continuous efforts in related fields. Summary of the invention
[0005] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.
[0006] The present disclosure provides a hard magnetic material with strong perpendicular magnetic anisotropy. The general formula of the material is R x A 1-x BO 2.5 , wherein R is a lanthanide element; the value of x is within a range of 0.01 to 0.50;
[0007] The A is selected from the group IIA elements, such as Ca and Sr, and the B is selected from the group 3d transition metal elements, such as Fe, Co and Ni;
[0008] Observing along the c-axis direction of the crystal structure, the atomic structure of the material is a structure in which a layer of Co-O tetrahedron and a layer of Co-O octahedron are alternately stacked (limonite structure).
[0009] In one embodiment provided in the present disclosure, the material is selected from Nd 0.1 Ca 0.9 CoO 2.5 ,La 0.1 Ca 0.9 CoO 2.5 、Sm 0.1 Ca 0.9 CoO 2.5 , Gd 0.1 Ca 0.9 CoO 2.5 、Dy 0.1 Ca 0.9 CoO 2.5 , Er 0.1 Ca 0.9 CoO 2.5 He Lu 0.1 Ca 0.9 CoO 2.5 Any one or more of La-based elements are doped.
[0010] In one embodiment provided by the present disclosure, the out-of-plane coercive field strength of the material is 15 kOe to 45 kOe (temperature is 100 K). The in-plane coercive field size is measured to exceed laboratory conditions (maximum laboratory field 7 T).
[0011] In another aspect, the present disclosure provides a method for preparing a hard magnetic material having strong perpendicular magnetic anisotropy, the method comprising:
[0012] Using R x A 1-x BO2.5 The target material is formed on the surface of the substrate by any of physical vapor deposition, chemical vapor deposition, electroplating, vacuum thermal evaporation, vacuum electron beam evaporation, DC sputtering, magnetron sputtering, radio frequency sputtering or pulsed laser deposition. x A 1-x BO 2.5 .
[0013] In one embodiment provided by the present disclosure, the R x A 1-x BO 2.5 The target material preparation method includes:
[0014] The oxides of R, A and B are separated according to R x A 1-x BO 2.5 The R x A 1-x BO 2.5 Target material;
[0015] In one embodiment provided by the present disclosure, the material of the substrate is selected from materials with any one orientation of (001), (110) and (111).
[0016] In one embodiment provided by the present disclosure, the substrate is selected from (001) oriented LaAlO3, (001) oriented (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 and one or more of the common orientations of common substrates such as (001)-oriented LaSrAlO4.
[0017] In one embodiment provided by the present disclosure, the epitaxial relationship between the film and the substrate is that the c-orientation of the limonite structure of the film is epitaxially extended along the normal direction of the substrate.
[0018] In another aspect, the present disclosure provides a method for regulating the saturation magnetization intensity of the hard magnetic material having strong perpendicular magnetic anisotropy, wherein the method is through temperature regulation;
[0019] When the magnetic field strength remains unchanged, the lower the temperature, the greater the saturation magnetization intensity of the material and the greater the coercive field;
[0020] When the temperature remains constant, the saturation magnetization is insensitive to the strength of the applied magnetic field.
[0021] Adjusting the type of rare earth element R used for doping can control the out-of-plane coercive field, among which Gd doping corresponds to the largest coercive field, and the corresponding increase or decrease of the R atomic number will reduce the out-of-plane coercive field;
[0022] The out-of-plane saturation magnetization intensity can be controlled by adjusting the type of rare earth element R used for doping. Among them, the out-of-plane saturation magnetization intensity of Nd doping is the largest, and the corresponding increase or decrease of R atomic number will reduce the out-of-plane saturation magnetization intensity.
[0023] On the other hand, the embodiments of the present disclosure provide applications of the above-mentioned materials in any one or more of logic devices, memory devices, electromagnetic wave transmitters, electromagnetic wave receivers, magnetic force microscopes, energy storage and storage devices.
[0024] The beneficial effects of the present disclosure over the prior art include:
[0025] The present disclosure provides a new type of hard magnetic material with extremely strong perpendicular magnetic anisotropy, provides a new approach to prepare such material, and provides controllable modulation of the strong magnetic anisotropy and saturation magnetization intensity in the material.
[0026] Other features and advantages of the present disclosure will be described in the following description, and partly become apparent from the description, or be understood by implementing the present disclosure. Other advantages of the present disclosure can be invented and obtained by the schemes described in the description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings are used to provide an understanding of the technical solution of the present disclosure and constitute a part of the specification. Together with the embodiments of the present disclosure, they are used to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.
[0028] Figure 1 The R provided by the present disclosure 0.1 A 0.9 BO 2.5 Schematic diagram of the atomic structure.
[0029] Figure 2 CaCoO on LaAlO3(001) substrate 2.5 and Nd 0.1 Ca 0.9 CoO 2.5 XRD of thin films, 2θ / ω scan.
[0030] Figure 3 Nd 0.1 Ca 0.9 CoO 2.5 Curves of film magnetization intensity (M) changing with magnetic field (H) and temperature (T). Figure 3(a) is a schematic diagram of the test results of the heating process under a 1kOe magnetic field after the temperature drops from room temperature to 10K at 70kOe. Figure 3 The corresponding test temperature in (b) is 100K.
[0031] Figure 4 When R is 100K 0.1 Ca 0.9 CoO 2.5 The maximum magnetic energy product of R = La, Nd, Sm, Gd, Dy, Er.
[0032] Figure 5 For R 0.1 Ca 0.9 CoO 2.5 Curve of film magnetization intensity (M) versus magnetic field (H), corresponding to a test temperature of 100K, where R = La, Nd, Sm, Gd, Dy, Er, Lu. DETAILED DESCRIPTION
[0033] To make the purpose, technical solution and advantages of the present disclosure more clear, the embodiments of the present disclosure are described in detail below. It should be noted that the embodiments and features in the embodiments of the present disclosure can be combined with each other arbitrarily without conflict.
[0034] The R used in the embodiments and comparative examples of the present disclosure 0.1 A 0.9 BO 2.5 The target material preparation method includes:
[0035] The oxides of R, A and B are separated according to R x A 1-x BO 2.5 The mixed powders are uniformly mixed according to the stoichiometric ratio, pressed into a certain shape and size, sintered at 1200°C in an atmospheric environment for 12 hours, and then annealed at a rate of 200°C / h to obtain the R x A 1-x BO 2.5 Target material.
[0036] Embodiment 1:
[0037] Preparation of thin film ferrimagnetic semiconductor material Nd on the LaAlO3 (001) substrate 0.1 Ca 0.9 CoO 2.5 , the atomic structure of the material is as follows Figure 1 As shown, along the c-axis direction of the crystal structure, the grown Nd 0.1 Ca 0.9 CoO 2.5The structure has a layer of Co-O tetrahedron and a layer of Co-O octahedron alternately stacked, wherein 10% of the Ca ions at the A position are replaced by La ions to present preferential site doping.
[0038] The preparation method uses a component of Nd 0.1 Ca 0.9 CoO 2.5 The solid solution target is used to grow Nd 0.1 Ca 0.9 CoO 2.5 Thin film. Nd 0.1 Ca 0.9 CoO 2.5 The thickness of the La-based element is 2 nm to 1000 nm. Other doping materials with the same proportion of La-based elements have similar properties.
[0039] Embodiment 2:
[0040] The ferrimagnetic semiconductor material prepared on the LaAlO3 (001) substrate using the process method of Example 1 is La 0.1 Ca 0.9 CoO 2.5 (Compared to Nd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), La 0.1 Ca 0.9 CoO 2.5 It also has strong perpendicular anisotropy and exhibits hard magnetic properties.
[0041] Embodiment 3:
[0042] The ferrimagnetic semiconductor material prepared on the LaAlO3 (001) substrate using the process method of Example 1 is Sm 0.1 Ca 0.9 CoO 2.5 (Compared to Nd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Sm 0.1 Ca 0.9 CoO 2.5 It also has strong perpendicular anisotropy and exhibits hard magnetic properties.
[0043] Embodiment 4:
[0044] The ferrimagnetic semiconductor material prepared on the LaAlO3 (001) substrate using the process method of Example 1 is Gd 0.1 Ca 0.9 CoO 2.5 (Compared to Nd in Example 10.1 Ca 0.9 CoO 2.5 have the same crystal structure), Gd 0.1 Ca 0.9 CoO 2.5 It also has strong perpendicular anisotropy and exhibits hard magnetic properties.
[0045] Embodiment 5:
[0046] The ferrimagnetic semiconductor material prepared on the LaAlO3 (001) substrate using the process method of Example 1 is Dy 0.1 Ca 0.9 CoO 2.5 (Compared to Nd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Dy 0.1 Ca 0.9 CoO 2.5 It also has strong perpendicular anisotropy and exhibits hard magnetic properties.
[0047] Embodiment 6:
[0048] The ferrimagnetic semiconductor material prepared on the LaAlO3 (001) substrate using the process method of Example 1 is Er 0.1 Ca 0.9 CoO 2.5 (Compared to Nd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Er 0.1 Ca 0.9 CoO 2.5 It also has strong perpendicular anisotropy and exhibits hard magnetic properties.
[0049] Embodiment 7:
[0050] The ferrimagnetic semiconductor material prepared on the LaAlO3 (001) substrate using the process method of Example 1 is Lu 0.1 Ca 0.9 CoO 2.5 (Compared to Nd in Example 1 0.1 Ca 0.9 CoO 2.5 have the same crystal structure), Lu 0.1 Ca 0.9 CoO 2.5 It also has strong perpendicular anisotropy and exhibits hard magnetic properties. Other materials doped with La-based elements in the same proportion have similar properties.
[0051] Comparative Example 1:
[0052] The difference between this comparative example and Example 1 is that the material is Nd 0.1 Ca 0.9 CoO 2.5 Modified to Pr 0.6 Ca 0.4 CoO 2.5 , the other processes are exactly the same as in Example 1. The obtained product does not have the corresponding effect. The crystal structure is the same as Nd 0.1 Ca 0.9 CoO 2.5 , does not have strong perpendicular anisotropy and hard magnetic properties.
[0053] Comparative Example 2:
[0054] The difference between the comparative example and the embodiment 1 is that the material is Nd 0.1 Ca 0.9 CoO 2.5 Modified to CaCoO 2.5 , the other processes are exactly the same as in Example 1. The obtained product does not have the corresponding effect. The crystal structure is the same as Nd 0.1 Ca 0.9 CoO 2.5 , does not have strong perpendicular anisotropy and hard magnetic properties.
[0055] Figure 2 , Figure 3 and Figure 4 The specific experimental data are all taken from the Nd prepared in Example 1. 0.1 Ca 0.9 CoO 2.5 The film and other doped materials with La series elements in the same proportion have similar properties.
[0056] By using the 2θ / ω scan of an X-ray diffractometer (XRD), information about the out-of-plane lattice period of the entire sample can be obtained. Figure 2 As shown, CaCoO grown on LaAlO3(001) substrate 2.5 Film, and R after 10% La-based element doping 0.1 Ca 0.9 CoO 2.5 (R = La-based element Nd) film. According to the Bragg diffraction formula, the out-of-plane lattice constant changes from 1.504nm to 1.516nm after 10% La-based element doping. Considering the larger radius of La ions and the doping effect of the charge itself, this result shows that the solution provided by the present disclosure successfully treats CaCoO 2.5 10% La-based element doping was performed, and uniform and high-quality R 0.1 Ca 0.9CoO 2.5 (R=La-based element Nd) thin film.
[0057] The R 0.1 Ca 0.9 CoO 2.5 The macroscopic magnetic properties of the (R = La-based element Nd) film were measured, and the experimental results are as follows Figure 3 As shown in Figure 2, the material exhibits strong perpendicular anisotropy. Figure 3 (b) is the hysteresis loop of the magnetization intensity (M) changing with the magnetic field (H) at 100K. Its out-of-plane coercive field is about 35kOe and its saturation magnetic moment is about 110emu / cc. The in-plane hysteresis loop shows that the magnetic field of 70kOe is far from saturating its magnetic moment. The in-plane and out-of-plane hysteresis loop results show that R 0.1 Ca 0.9 CoO 2.5 It has a very strong perpendicular magnetic anisotropy, and its out-of-plane coercive field of 35kOe also shows that R 0.1 Ca 0.9 CoO 2.5 It is an excellent hard magnetic material. Its perpendicular magnetic anisotropy and hard magnetic properties are widely used in the fields of spin electronics, magnetic recording media and permanent magnetic materials. The ferromagnetic transition temperature of this material is Figure 3 (a) is shown at about 250K.
[0058] According to the existing magnetic data, R 0.1 Ca 0.9 CoO 2.5 The maximum magnetic energy product result is as follows: Figure 4 The maximum magnetic energy product is a key parameter to measure the performance of permanent magnet materials. The maximum magnetic energy product of NdFeB, the most excellent permanent magnet, has a peak value of about 56MGOe at around 100K. The results show that R 0.1 Ca 0.9 CoO 2.5 The maximum magnetic energy product is about 20MGOe (100K), and it will increase further with the decrease of temperature. 0.1 Ca 0.9 CoO 2.5 It is a potential permanent magnetic (hard magnetic) material with superior performance and has a wide range of application scenarios in the field of permanent magnetic materials.
[0059] Permanent magnetic materials are widely used in the design, development and manufacture of various electronic products, such as DVDs, cameras, sensors and mobile phones. All of these devices include components of permanent magnets, such as the vibration motor in a mobile phone. High magnetic energy product magnets make the miniaturization of these devices possible. x A1-x BO 2.5 It is a potential permanent magnetic (hard magnetic) material with superior performance. In low temperature scenarios, R x A 1-x BO 2.5 The superior hard magnetic properties can also be used as strong magnets in the above-mentioned electronic devices.
[0060] In addition, perpendicular magnetic anisotropy materials are one of the best candidates for magnetic storage applications. Compared with traditional random access memories such as dynamic random access memory (DRAM), magnetic random access memory (MRAM) has the characteristics of fast read and write speed, large storage space, strong scalability, ultra-long durability and non-volatile data storage, and is an important direction for the current development of memory. The magnetic moment of a film with perpendicular magnetic anisotropy is parallel to the normal direction of the film. Compared with materials with in-plane magnetization, it has a higher storage density and contributes to the further miniaturization of storage devices. Currently, common perpendicular magnetic anisotropy materials include multilayer film structures such as CoFeB / MgO, but the multilayer film itself has a complex structure. The R x A 1-x BO 2.5 The material has extremely strong perpendicular magnetic anisotropy in its operating temperature range, and its anisotropy is an intrinsic property of the film, which will have broad application prospects in devices such as magnetic random access memory.
Claims
1. A hard magnetic material with strong perpendicular magnetic anisotropy, characterized in that: The general formula of the material is R x A 1-x BO 2.5 , wherein R is a lanthanide element; the value of x is within a range of 0.01 to 0.50; A is selected from the elements of the main group IIA, and B is selected from 3d transition metal elements; Observing along the c-axis direction of the crystal structure, the atomic structure of the material is a structure in which a layer of BO tetrahedrons and a layer of BO octahedrons are alternately stacked.
2. The hard magnetic material with strong perpendicular magnetic anisotropy according to claim 1, characterized in that: The material is selected from Nd 0.1 Ca 0.9 CoO 2.5 ,La 0.1 Ca 0.9 CoO 2.5 、Sm 0.1 Ca 0.9 CoO 2.5 , Gd 0.1 Ca 0.9 CoO 2.5 、Dy 0.1 Ca 0.9 CoO 2.5 , Er 0.1 Ca 0.9 CoO 2.5 He Lu 0.1 Ca 0.9 CoO 2.5 Any one or more of .
3. The method for preparing a hard magnetic material with strong perpendicular magnetic anisotropy according to claim 1 or 2, characterized in that: The preparation method comprises: Using R x A 1-x BO 2.5 The target material is formed on the surface of the substrate by any of physical vapor deposition, chemical vapor deposition, electroplating, vacuum thermal evaporation, vacuum electron beam evaporation, DC sputtering, magnetron sputtering, radio frequency sputtering or pulsed laser deposition. x A 1-x BO 2.5 .
4. The preparation method according to claim 3, characterized in that: The R x A 1-x BO 2.5 The target material preparation method includes: The oxides of R, A and B are separated according to R x A 1-x BO 2.5 The R x A 1-x BO 2.5 Target material.
5. The preparation method according to claim 3 or 4, characterized in that: The material of the substrate is selected from materials with any one of (001), (110) and (111) orientations.
6. The preparation method according to claim 3 or 4, characterized in that: The substrate is selected from YAlO3, SrTiO3, LaAlO3, (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 and one or more of LaSrAlO4.
7. The preparation method according to claim 3 or 4, characterized in that: The epitaxial relationship between the film and the substrate is that the c-orientation of the structure of the film is epitaxially extended along the normal direction of the substrate.
8. A method for regulating the saturation magnetization intensity of the hard magnetic material with strong perpendicular magnetic anisotropy as claimed in claim 1 or 2, characterized in that: The method comprises: When the magnetic field strength remains unchanged, the lower the temperature, the greater the saturation magnetization intensity of the material and the greater the coercive field.
9. Application of the material according to claim 1 or 2 in any one or more of logic devices, memory devices, electromagnetic wave transmitters, electromagnetic wave receivers, magnetic force microscopes, energy storage and storage devices.
Citation Information
Patent Citations
Preparation method of doped magnetic semiconductor gradient material
CN105575771A
Hydrogen-containing transition metal oxide, preparation method and primary battery
CN108091870A
Novel bismuth iron oxide room temperature multiferroic magnetoelectric coupling material, preparation method of coupling material and electronic device
CN109809493A
Ferromagnetic material, preparation method thereof and sensor
CN110580995A
Magnetic bubble devices with controlled temperature characteristics
US4002803A